The cranial osteology revealed by three-dimensionally preserved skulls of the Early Triassic ichthyosauriform Chaohusaurus chaoxianensis (Reptilia: Ichthyosauromorpha) from Anhui, China. Issue 4 (4th July 2017) - Zhou, Min; Jiang, Da-Yong; Motani, Ryosuke; Tintori, Andrea; Ji, Cheng; Sun, Zuo-Yu; Ni, Pei-Gang; Lu, Hao
ABSTRACT: Chaohusaurus is one of the earliest-branching ichthyosauriforms, but its cranial anatomy remains poorly known due to the lack of well-preserved material. Here, three nearly complete and well-preserved skulls of C. chaoxianensis are described, revealing new information on the cranial anatomy of the species. The prefrontal-postfrontal contact is clearly present in C. chaoxianensis, unlike in Cartorhynchus and basal Hupehsuchia. The squamosal and postorbital participate in the margin of the upper temporal fenestra as in most basal ichthyosauriforms. The postorbital region is narrow, with a deep ventral embayment representing an incomplete lower temporal fenestra. Three-dimensional preservation revealed that the posterior cheek region curves and faces almost posteriorly, whereas the orbit is directed slightly dorsally rather than strictly laterally. The cranial morphology of Chaohusaurus confirms the suggestion that the elongation of the nasal and posterior relocation of the external naris preceded snout elongation in ichthyosauriforms.